Pemberian diet ekstra formula komersial dan diet ekstra filtrat ikan gabus intradialisis serta pengaruhnya terhadap kadar serum albumin dan kreatinin pasien dengan hemodialisis di RSU Dr. Saiful Anwar Malang - Etik Sulistyowati; Hamam Hadi; Susetyowati Susetyowati; Atma Gunawan (Jurnal Gizi Klinik Indonesia, 2008)
Background: Nowadays chronic kidney disease (CKD) is a serious health problem because of its increasing incidence. In Indonesia, approximately there are 100 CKD patients per 1 million people per year. Hemodialysis is one of ways to prolong CKD patient’s life that should be done recurrently and for a long time. However, hemodialysis causes loss of nutrients leading to high prevalence of malnutrition among CKD patients. Until today intradialysis diet therapy which can replace loss of nutrients particularly protein has not been initiated as part of diet therapy in Indonesian hospitals. To improve nutritional status and minimize mortality rate, oral intradialysis diet therapy with proper formula is needed.Objective: To study the effect of the supply of commercial formula and local catfish filtrate extra diet to albumin and creatinine serum level among hemodialysis patients.Method: The study was experimental with randomized control trial design carried out at Dialysis Installation of Dr. Saiful Anwar Hospital, Malang. There were as many as 36 hemodialysis patients divided into 3 groups; 1 group with standard diet, 1 group with commercial formula and standard diet, and 1 group with local catfish filtrate and standard diet. Data were obtained through interview, note taking, and laboratory tests which consisted of subject characteristics in weight, height, albumin and creatinin serum level as well as food intake one day before, during and one day after hemodialysis. Data analysis was done descriptively and inferentially using chi square, anova, and paired t-test. The conclusion was based on significance level (α ) 0.05 or p < 0.05.Results: There was no significant difference in the characteristics of the subject at the beginning of the study with average albumin serum level 3.61 ± 0.48 g/dL and creatinine serum level 9.04 ± 2.73 mg/dL. There was no difference in average energy and protein intake of the subject. At the end of the study average albumin serum level was 3.38 ± 0.42 g/dL, creatinine serum level 8.34 ± 3.6 mg/dL, and there was significant difference in albumin serum level (p = 0.000) of the subject. Although there was an increase of creatinine serum level in the group with local catfish filtrate extra diet, it was statistically insignificant.Conclusion: There was significant effect of the supply of commercial formula and local catfish filtrate extra diet to increase of albumin serum level of the subject and there was no significant effect of the supply of extra diet to creatinine serum level; however, the supply of local catfish filtrate extra diet could maintain creatinine serum level.